(3CSGSjGJ aj GdehGQO GdEbJUGOjIs - (3YHO GdeWdH(B, (3YHO GdMejOs; (3eMeO(B, (3TGHIs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2005)
(3GdehGQO GdEbJUGOjI ef MjK GdJYQja hGdCgejI(B- (3GdJbSjeGJ GdeNJdaI ddehGQO GdEbJUGOjI(B- (3EbJUGOjGJ hJNWjW hJfejI GdehGQO GdHTQjI(B-(3GbJUGOjGJ GdJYdje hGdESJKeGQ aj GdehGQO GdHTQjI(B- (3GbJUGOjGJ GdScGf hGdJfejI(B- (3GSJQGJjLjI GdJfejI aj LfhH GdhGOj hCgOGag(B- (3GdehGQO GdeYOfjI(B- (3ehGQO GdWGbI hGdHJQhd(B- (3GdehGQO GdWHjYjI aj LeghQjI eUQ GdYQHjI(B- (3eTcdGJ GNJdGd GdYdGbI Hjf GdHjFI hGdJfejIs
Keywords: (3GdehGQO GdEbJUGOjIs